Case study on the artiste management industry - OM artistes. - Muhammad Asril Ibrahim. (2008)
This study looks into the burgeoning industry of artiste management and intensely studies one of the players in that industry. At the end of this study, recommendations were proposed to the artiste management agency in question in terms of strategy and marketing.